Comparison of Tastes of Available Nutritional Integrated or Non-Integrated Formulas for Infants Older Than 1 Year of Age With Cow's Milk Allergy: A Multicenter, Prospective, Single Blind, Cross-Sectional Observational Clinical Study (Contest Study) - Altintas, Derya Ufuk; Turktas, Ipek; Arga, Mustafa; Cokugras, Haluk Cezmi; Civelek, Ersoy; Keskin, Ozlem; Guler, Nermin (Codon Publications, 2022)
Palatability of the infant formulas lacking cow milk protein formulas is reported by parents to be an important drawback. The purpose of this study is to examine decisions made by mothers of infants having cow milk protein allergy, and physicians concerning the palatability of unflavored extensively hydrolyzed formulas and amino acid-based formulas. We conducted a multi-center, randomized, single-blinded, observational taste study involving 149 pediatricians from gastroenterology and allergy subspecialties at 14 tertiary healthcare units from different regions of Turkey and involving 94 mothers of infants with cow milk protein allergy. Blinding was performed for seven formulas available in the market, which were the most commonly prescribed for feeding: four AAFs (Neocate-Numil((R)), Aptamil Pregomin AS-Numil((R)), Alfamino-Nestle((R)), Comidagen-Mamma((R))), one AAF specifically designed to address the growing nutritional and lifestyle needs of children >1 year (Neocate Junior-Numil((R))), 2 eHFs (Bebelac Pepti Junior-Numil((R)), Similac Alimentum-Abott((R))). Considering all three formula characteristics, Neocate junior-Numil((R)) ranked as the number 1 product among seven products by mothers (63.8%) and physicians (69.8%). The ratings of mothers were significantly higher than the physicians (8.1 points and 6.1 points, respectively; p < 0.001). No difference was found in terms of taste, smell, and appearance for Neocate junior-Numil((R)) between the mothers' and physicians' ratings. Since caregivers have responsibility for careful selection of replacement products for infants with cow milk protein allergy, it is noteworthy that increased awareness and confidence in the palatability characteristics of these products should motivate mothers and physicians to comply with replacement treatment in the long term. (c) 2022 Codon Publications. Published by Codon Publications.
Ertem, Deniz/0000-0002-4427-0569; Buyuktiryaki, Betul/0000-0003-1206-969X; Yucel, Esra/0000-0003-3712-2522; Cokugras, Haluk Cezmi/0000-0002-0086-3936; Ecevit, Çiğdem Ömür/0000-0002-3980-8686
Keywords: Cow's Milk Protein Allergy; Taste Perception; Protein Hydrolysates; Infant Formula; Compliance